Protocatechuic acid inhibits proliferation, migration and inflammatory response in rheumatoid arthritis fibroblast-like synoviocytes. Issue 1 (1st January 2020) - Wu, Huiqiang; Wang, Jing; Zhao, Qing; Ding, Yanjie; Zhang, Bingyi; Kong, Lingli
Abstract: Rheumatoid arthritis (RA) is a chronic joint inflammatory disease that is closely associated with dysregulation of fibroblast-like synoviocytes (FLSs). Protocatechuic acid (PCA), a phenolic compound of anthocyanins, has been proven to possess anti-inflammatory activity. However, the role of PCA in RA has not been investigated. In the present study, we aimed to explore the effects of PCA on the RA-FLSs. The results showed that PCA suppressed the proliferation, invasion, and migration of RA-FLSs in a dose-dependent manner. PCA treatment also inhibited the expressions of matrix metalloproteinase (MMP)-3 and MMP-13, as well as the secretion of inflammatory cytokines including TNF-α, IL-1β, IL-6 in RA-FLSs. Moreover, cell apoptosis of RA-FLSs was significantly induced by PCA treatment. PCA was found to repress the activation of NF-κB signalling, which was evidenced by the decreased expression of p-p65 and increased expression of IκBα. Furthermore, PCA significantly decreased the phosphorylation levels of Akt and mTOR in RA-FLSs. In conclusion, the results indicated that PCA exhibited an inhibitory effect on RA-FLSs via inhibiting the NF-κB and Akt/mTOR signalling pathways. These findings supported the concept that PCA might be a therapeutic agent for RA treatment.